An ultrasonic-assisted powder-solid coupling forming method of silicon carbide fiber reinforced titanium matrix composite

CN122941970APending Publication Date: 2026-10-20BEIHANG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611268641.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

但是,通过常规的升温加压方法难以使粉末完全填充到束丝/编织纤维的间隙,粉末致密度提高程度有限,导致钛基复合材料中不可避免地存在微孔洞等缺陷

Benefits of technology

本发明提供了一种碳化硅纤维增强钛基复合材料的超声辅助粉固耦合成形方法,通过粉固耦合(同时以钛基粉末和钛基箔材为基体,适用于束丝纤维)结合超声振动(改善粉末填充性和致密性、界面结合、提升性能),利用加速颗粒重排、抑制界面缺陷和损伤、软化效应和热效应等作用机制,改善钛合金基体粉末填充性和致密性,以及钛合金基体与碳化硅纤维的界面结合,提升成形性能和力学性能,是钛基复合材料的成形新方法,具有以下优势:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of titanium-based composite material preparation technology, and more particularly to an ultrasonic-assisted powder-solid coupling forming method for silicon carbide fiber-reinforced titanium-based composite materials. This invention provides an ultrasonic-assisted powder-solid coupling forming method for silicon carbide fiber-reinforced titanium-based composite materials. By combining powder-solid coupling (using both titanium-based powder and titanium-based foil as the matrix, suitable for bundled fibers) with ultrasonic vibration (improving powder filling and density, interfacial bonding, and performance enhancement), and utilizing mechanisms such as accelerated particle rearrangement, suppression of interfacial defects and damage, softening effect, and thermal effect, it improves the filling and density of the titanium alloy matrix powder, as well as the interfacial bonding between the titanium alloy matrix and silicon carbide fibers, thereby enhancing forming performance and mechanical properties. This provides a novel method for forming titanium-based composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of titanium-based composite material preparation technology, and in particular to an ultrasonic-assisted powder-solid coupling forming method for silicon carbide fiber reinforced titanium-based composite materials. Background Technology

[0002] Hypersonic vehicles represent a new pinnacle in aerospace technology development. When flying at high Mach numbers, the surface temperature of their skin rises dramatically due to intense aerodynamic heating, necessitating lightweight, high-temperature resistant materials. Silicon carbide (SiC) fiber-reinforced titanium matrix composites, with their low density and excellent high-temperature performance, are ideal material choices for hypersonic vehicle skins. Furthermore, compared to commonly used silicon carbide fibers prepared by chemical vapor deposition (CVD), silicon carbide fibers prepared by polymer-derived (PD) methods are lower in cost, more flexible, and can be woven into various fabrics to achieve quasi-isotropic properties. Therefore, polymer-derived silicon carbide fiber-reinforced titanium matrix composites have significant application potential in hypersonic vehicle skins.

[0003] The mainstream preparation process for titanium-based composites is the solid-state method. However, silicon carbide fibers prepared by the precursor conversion method are in bundle form, and conventional matrix forms (such as foils) are difficult to penetrate into the bundle fibers. This makes traditional preparation and forming methods (such as foil-fiber-foil methods) incompletely applicable, and fiber coating methods using magnetron sputtering technology are also difficult to handle bundle fibers. Powders have good flowability and can effectively penetrate into and bond with silicon carbide bundle fibers. However, conventional heating and pressurizing methods are insufficient to completely fill the gaps between bundle / braided fibers with powder, resulting in limited improvement in powder density and inevitably leading to defects such as micropores in titanium-based composites.

[0004] For example, Chinese patent CN122327107A discloses a method for preparing a continuous silicon carbide fiber reinforced titanium matrix composite material plate, which uses a rapid sintering method to avoid the problem of large interfacial reactions during traditional preparation methods and has a shorter cycle time. However, this method involves coating a titanium alloy matrix onto the surface of silicon carbide fibers (i.e., fiber coating method), which cannot handle bundled fibers. Chinese patent CN120756182A discloses a method for preparing an ultrathin laminate of silicon carbide fiber reinforced titanium matrix composite material, which can reduce the warping of the composite laminate and make the fibers uniformly dispersed. However, the main matrix used in this method is titanium alloy foil (i.e., foil-fiber-foil method), which cannot enter the gaps between bundled fibers. Chinese patent CN116329555A discloses a method for preparing a silicon carbide braided fiber reinforced titanium matrix composite material plate, which uses titanium alloy powder instead of titanium alloy foil as the matrix, allowing the titanium alloy matrix to enter the gaps inside the braided fibers and overcoming the disadvantage of poor flowability of titanium alloy foil. However, conventional heating and pressurization methods cannot effectively fill the gaps with titanium alloy matrix.

[0005] Therefore, how to better integrate the titanium alloy matrix into the gaps between the bundled fibers to obtain high-performance dense composite materials is an urgent problem to be solved in this field. Summary of the Invention

[0006] In view of this, the present invention provides an ultrasonic-assisted powder-solid coupling forming method for silicon carbide fiber reinforced titanium matrix composites. The ultrasonic-assisted powder-solid coupling forming method provided by the present invention uses ultrasonic assistance at high temperature and high pressure to improve the filling and compactness of titanium alloy matrix powder and the interfacial bonding between titanium alloy matrix and silicon carbide fiber through mechanisms such as accelerating particle rearrangement, suppressing interface defects and damage, softening effect and thermal effect, thereby improving forming performance and mechanical properties.

[0007] This invention provides an ultrasonic-assisted powder-solid coupling forming method for silicon carbide fiber-reinforced titanium matrix composites, comprising the following steps: (1) Cut silicon carbide fibers to the same length as titanium-based foil, then spread titanium-based powder on the surface of silicon carbide fibers and vibrate to obtain a mixture of titanium-based powder and silicon carbide fibers; (2) The titanium-based foil, titanium-based powder, titanium-based powder-silicon carbide fiber mixture, titanium-based powder and titanium-based foil are stacked in the order of titanium-based foil to obtain the preform; (3) The preform is sequentially sealed, resisted, ultrasonically vibrated hot pressing and furnace cooling to obtain silicon carbide fiber reinforced titanium matrix composite material.

[0008] Preferably, the silicon carbide fiber is prepared by precursor conversion method; the silicon carbide fiber is in the form of bundle or braid; the thickness of the silicon carbide fiber (the thickness laid on the vibration table used for vibration) is 0.01~1 mm.

[0009] Preferably, the particle size of the titanium-based powder is no greater than 53 micrometers.

[0010] Preferably, the vibrating device is a vibration table; the vibration direction is horizontal and unidirectional, the vibration frequency is 30~50Hz, the vibration amplitude is 0.4~0.7 mm, and the vibration time is 30~60 seconds.

[0011] Preferably, the number of stacking cycles is more than 1; when the number of stacking cycles is more than 2, the same layers are not adjacent (i.e., two layers of the same material are not placed consecutively, for example, when two layers of titanium-based aluminum foil are adjacent, only one layer of titanium-based aluminum foil is placed).

[0012] Preferably, the sealing is performed using vacuum electron beam sealing; the accelerating voltage is 50~150kV, the electron beam current is 10~50mA, the focusing current is 200~500mA, the welding speed is 500~1500mm / min, the scanning frequency is 100~300Hz, the amplitude is 20~50mm, and the vacuum level is not less than 5×10 -2 Pa.

[0013] Preferably, ultrasonic vibration-assisted hot pressing includes the following steps: ultrasonic vibration filling of the preform after resist welding, pre-compression, vacuuming, powder degassing, fiber degumming and hot pressing.

[0014] Preferably, the ultrasonic vibration powder filling direction is horizontal and unidirectional, the vibration frequency is 20~30kHz, the vibration amplitude is 20~50 micrometers, and the ultrasonic vibration powder filling time is 30~60 seconds.

[0015] Preferably, the hot pressing includes a heating and pressurizing stage and a heat preservation and pressure holding stage; the heating rate of the heating and pressurizing stage is 5~20℃ / min; the temperature of the heat preservation and pressure holding stage is 800~1000 degrees Celsius, the pressure (normal pressure on the preform) is 20~100MPa, and the time is 1~5 hours; the hot pressing is carried out under ultrasonic vibration conditions; the vibration frequency of the ultrasonic vibration is 20~25kHz, the vibration amplitude is 10~30 micrometers, and the vibration mode is intermittent vibration; the intermittent vibration mode is: vibrating for 30 seconds every 10 minutes.

[0016] Preferably, the furnace cooling includes a pressure holding and cooling stage (referred to as the first pressure holding and cooling stage), a pressure reduction and cooling stage, and a pressure holding and cooling stage (referred to as the second pressure holding and cooling stage); the pressure of the first pressure holding and cooling stage is 20~100MPa; the final temperature of the cooling and depressurization stage is 300~500 degrees Celsius; and the pressure of the second pressure holding and cooling stage is 5~20t.

[0017] Compared with the prior art, the present invention has achieved the following beneficial effects: This invention provides an ultrasonic-assisted powder-solid coupling forming method for silicon carbide fiber-reinforced titanium matrix composites. By combining powder-solid coupling (using both titanium-based powder and titanium-based foil as the matrix, suitable for bundled fibers) with ultrasonic vibration (improving powder filling and density, interfacial bonding, and performance enhancement), and utilizing mechanisms such as accelerated particle rearrangement, suppression of interfacial defects and damage, softening effect, and thermal effect, the method improves the filling and density of the titanium alloy matrix powder, as well as the interfacial bonding between the titanium alloy matrix and silicon carbide fibers, thereby enhancing forming performance and mechanical properties. This is a novel forming method for titanium-based composite materials and has the following advantages: (1) Achieving low-cost quasi-isotropic silicon carbide fiber reinforced titanium matrix composite material forming: Compared with the commonly used chemical vapor deposition silicon carbide fiber reinforced titanium matrix composite material, the precursor conversion silicon carbide fiber reinforced titanium matrix composite material formed by the present invention has low cost and can use various forms of silicon carbide fiber fabric to achieve quasi-isotropy.

[0018] (2) Ultrasonic vibration promotes the filling of titanium alloy matrix powder: Ultrasonic vibration can weaken the frictional resistance between titanium alloy matrix powder particles, accelerate the particle rearrangement process, promote the flow of titanium alloy matrix powder, and enable the titanium alloy matrix powder to enter the gap inside the bundled fiber well. This helps to improve the flow and filling effect of titanium alloy matrix powder in bundled / braided fiber, increase the density of silicon carbide fiber reinforced titanium matrix composites and reduce porosity.

[0019] (3) Ultrasonic vibration promotes densification of titanium alloy matrix powder: Ultrasonic vibration can promote the creep and superplastic flow of titanium alloy matrix powder at high temperature, and improve the metallurgical densification of titanium alloy matrix powder.

[0020] (4) Ultrasonic vibration improves interfacial bonding: Ultrasonic vibration can reduce local stress concentration during the forming process, inhibit the formation and propagation of fiber / matrix interface cracks and defects; promote the breakage of surface oxide layer, drive the formation of nanoscale grains in interface reaction layer, inhibit interface brittle damage, improve interface toughness, and improve the interfacial bonding of silicon carbide fiber reinforced titanium matrix composites.

[0021] (5) Ultrasonic vibration improves the deformation capacity and mechanical properties of silicon carbide fiber reinforced titanium matrix composites: Ultrasonic vibration suppresses anisotropy through local thermal effect and dynamic recrystallization mechanism, effectively reduces the brittleness of silicon carbide fiber reinforced titanium matrix composites, and improves plastic deformation capacity; it refines material grains, avoids grain coarsening and uneven distribution, suppresses the generation of internal defects, and significantly improves the mechanical properties of silicon carbide fiber reinforced titanium matrix composites. Attached Figure Description

[0022] To more clearly illustrate the technical solutions of this invention, the accompanying drawings used in the embodiments of this invention or in the prior art are briefly described below. For those skilled in the art, other drawings can be derived from the following drawings without creative effort, and all such drawings are within the protection scope of this invention.

[0023] Figure 1 A process flow diagram of the ultrasonic-assisted powder-solid coupling forming method for silicon carbide fiber reinforced titanium matrix composites provided by the present invention; Figure 2 This is a schematic diagram illustrating the operation of the ultrasonic-assisted powder-solid coupling forming method for silicon carbide fiber-reinforced titanium matrix composites provided by the present invention. Figure labels: 1 is the middle titanium-based foil, 2 is the titanium-based foil at both ends, 3 is silicon carbide fiber, 4 is titanium-based powder, 5 is the pressure head (upper and lower), and 6 is the ultrasonic device; Figure 3 The microstructure of titanium-based powder of the silicon carbide fiber-reinforced titanium-based composite material prepared in Example 1 of this invention; Figure 4 The microstructure of the radial interfacial bonding of the silicon carbide fiber-reinforced titanium matrix composite material prepared in Example 1 of the present invention; Figure 5 The image shows the microstructure of the axial interfacial bonding of the silicon carbide fiber-reinforced titanium matrix composite material prepared in Example 1 of this invention. Detailed Implementation

[0024] This invention provides an ultrasonic-assisted powder-solid coupling forming method for silicon carbide fiber-reinforced titanium matrix composites, comprising the following steps: (1) Cut silicon carbide fibers to the same length as titanium-based foil, then spread titanium-based powder on the surface of silicon carbide fibers and vibrate to obtain a mixture of titanium-based powder and silicon carbide fibers; (2) The titanium-based foil, titanium-based powder, titanium-based powder-silicon carbide fiber mixture, titanium-based powder and titanium-based foil are stacked in the order of titanium-based foil to obtain the preform; (3) The preform is sequentially sealed, resisted, ultrasonically vibrated hot pressing and furnace cooling to obtain silicon carbide fiber reinforced titanium matrix composite material.

[0025] like Figure 1 As shown, in this invention, silicon carbide fibers are cut to the same length as titanium-based foil, and then titanium-based powder is spread on the surface of silicon carbide fibers and vibrated to obtain a mixture of titanium-based powder and silicon carbide fibers.

[0026] In this invention, the titanium-based foil material can be pure titanium, titanium alloy, or titanium-aluminum intermetallic compound.

[0027] In this invention, the thickness of the titanium-based foil can be 0.01 to 1 mm, specifically 0.05 mm, 0.1 mm, 0.3 mm, 0.5 mm or 0.8 mm.

[0028] In this invention, the titanium-based foil may include a middle titanium-based foil and two end titanium-based foils. The middle titanium-based foil is used in the middle of the preform, and the two end titanium-based foils are used at both ends of the preform. The difference between the two lies in their size and position in the preform. The aforementioned silicon carbide fiber cut to the same length as the titanium-based foil refers to the middle titanium-based foil.

[0029] In this invention, the size of the intermediate titanium-based foil does not exceed the size of the pressure head of the hot pressing equipment, and the area of ​​the titanium-based foil satisfies Equation 1: Formula 1; In Equation 1, S The area (mm) of the intermediate titanium-based foil 2 ), F This refers to the maximum pressing force (N) of the pressure head of the hot press equipment. σ This is the minimum normal pressure (MPa) for hot pressing.

[0030] In this invention, the length of each side of the titanium-based foil at both ends is 2-10 mm longer than the length of each side of the titanium-based foil in the middle, specifically 5 mm or 8 mm. This invention ensures that the titanium-based foil at both ends has sufficient material to wrap around the sides of the preform, providing a material basis for subsequent sealing. The titanium-based foil of the aforementioned target dimensions is obtained by cutting.

[0031] In this invention, the titanium-based foil can be pretreated before use, and the pretreatment may include grinding and cleaning in sequence.

[0032] In this invention, the polishing equipment can be silicon carbide sandpaper; the grit of the silicon carbide sandpaper can be 500-2000 grit, specifically 500 grit, 1000 grit, 1500 grit, or 2000 grit; the polishing can include the following steps: polishing the titanium-based foil sequentially with low-grit and high-grit silicon carbide sandpaper. This invention removes the oxide film and impurities from various surfaces of the titanium-based foil through polishing.

[0033] In this invention, the cleaning can be ultrasonic cleaning; ultrasonic cleaning can include the following steps: immersing the polished titanium-based foil in an ultrasonic liquid and ultrasonically cleaning it; the ultrasonic cleaning equipment can include an ultrasonic cleaner; the ultrasonic liquid can include one or both of water and an organic solvent; the water can be deionized water; the organic solvent can be acetone or anhydrous ethanol; the ultrasonic cleaning temperature can be room temperature, the frequency can be 28~45kHz, specifically 30kHz, 33kHz, 36kHz, 40kHz or 43kHz, and the power density can be 0.5~0.8W / cm². 2 Specifically, it can be 0.6 W / cm 2 Or 0.7W / cm 2 The cleaning time can be 10 minutes or more. After cleaning, remove the titanium-based foil.

[0034] In this invention, the cleaning process may further include drying (referred to as first drying); the first drying may be carried out in a dust-free environment; the first drying may be natural drying or oven drying; the temperature of natural drying may be room temperature, and the time may be more than 20 minutes; the temperature of oven drying may be 40~60 degrees Celsius, specifically 50 degrees Celsius, and the time may be 10~20 minutes, specifically 15 minutes.

[0035] In this invention, the silicon carbide fiber can be silicon carbide fiber prepared by precursor conversion method; the silicon carbide fiber can be in the form of bundle or braid; the thickness of the silicon carbide fiber (the thickness laid on the vibration table used for vibration) can be 0.01~1 mm, specifically 0.05 mm, 0.1 mm, 0.3 mm, 0.5 mm or 0.7 mm.

[0036] In this invention, the material of the titanium-based powder can be the same as that of the titanium-based foil, which will not be described in detail here; the particle size of the titanium-based powder can be no greater than 53 micrometers, specifically 50 micrometers, 30 micrometers, 20 micrometers, 15 micrometers, 10 micrometers, 5 micrometers, 1 micrometer, 0.5 micrometers, 0.1 micrometers or 0.01 micrometers.

[0037] In this invention, the vibrating device can be a vibration table; the vibration direction can be horizontal and unidirectional; the vibration frequency can be 30~50Hz, specifically 40Hz; the vibration amplitude can be 0.4~0.7 mm, specifically 0.5 mm or 0.6 mm; and the vibration time can be 30~60 seconds, specifically 40 seconds or 50 seconds. This invention uniformly spreads titanium-based powder on the surface of silicon carbide fibers, and vibration causes the titanium-based powder to penetrate the silicon carbide fibers, achieving initial weight gain.

[0038] In this invention, the mass relationship between titanium-based powder and silicon carbide fiber (the mass of titanium-based powder entering the silicon carbide fiber) is shown in Equation 2: Formula 2; In Equation 2, m The weight (g) of titanium-based powder incorporated into silicon carbide fibers. ρ Density of titanium-based powder (g / cm³) 3 ), S The area (cm²) of silicon carbide fiber (or intermediate titanium-based foil) 2 ), t f The thickness (cm) of silicon carbide fiber (excluding titanium-based powder). δ Porosity of silicon carbide fibers (excluding titanium-based powder) r The value for powder density is 0.6 to 0.8.

[0039] After obtaining the titanium-based powder-silicon carbide fiber mixture, the present invention stacks titanium-based foil, titanium-based powder, titanium-based powder-silicon carbide fiber mixture, titanium-based powder, and titanium-based foil in the following order (e.g., Figure 2 As shown in the figure, the preform is obtained.

[0040] In this invention, the thickness of a single layer of titanium-based powder satisfies Equation 3: Formula 3; In Equation 3, t p The thickness (mm) of a single layer of titanium-based powder. t f The thickness (mm) of a single layer of silicon carbide fiber (excluding titanium-based powder). V f For the desired fiber volume fraction, t b The thickness (mm) of a single layer of titanium-based foil. L This refers to the number of layers in the silicon carbide fiber. M The number of layers in the titanium-based foil depends on the lamination relationship. M = L +1; N The number of layers in the titanium-based powder is determined by the stacking relationship. N =2 L The required fiber volume fraction satisfies equation 4: Equation 4; In Equation 4, σ 0 represents the required tensile strength (MPa) for silicon carbide fiber reinforced titanium matrix composites. K The interface is combined with a correction factor, which is 0.5 to 1.0, specifically 0.6 or 0.8; σ m The tensile strength (MPa) of the titanium-based powder. σ fThe tensile strength (MPa) of silicon carbide fiber.

[0041] In this invention, the thickness of a single layer of titanium-based powder can be controlled by weighing, i.e., the weight of a single layer of titanium-based powder satisfies Equation 5: Formula 5; In Equation 5, m 0 represents the weight (g) of a single layer of titanium-based powder. ρ Density of titanium-based powder (g / cm³) 3 ), S The area (cm²) of silicon carbide fiber (or intermediate titanium-based foil) 2 ), t p The thickness (cm) of a single layer of titanium-based powder.

[0042] In this invention, a roller can be used to level the titanium-based powder during application, and the thickness error of the titanium-based powder can not exceed 20% (the percentage of the error thickness to the target thickness). A clean roller is used to level the titanium-based powder during the application of each layer, ensuring that the thickness difference of each layer does not exceed 20% of the thickness of the previous layer.

[0043] In this invention, the stacking cycle can be repeated more than once; when the stacking cycle is repeated more than twice, identical layers are not adjacent (i.e., two layers of the same material are not placed consecutively; for example, when two layers of titanium-based aluminum foil are adjacent, only one layer of titanium-based aluminum foil is placed). This invention can be repeated in the above order for more than one set.

[0044] After obtaining the preform, the present invention sequentially performs sealing welding, resist welding, ultrasonic vibration-assisted hot pressing, and furnace cooling on the preform to obtain a silicon carbide fiber-reinforced titanium matrix composite material. In this invention, the sealing welding can be vacuum electron beam sealing welding; the accelerating voltage of the sealing welding can be 50~150kV, specifically 100kV; the electron beam current can be 10~50mA, specifically 20mA, 30mA, or 40mA; the focusing current can be 200~500mA, specifically 300mA or 400mA; the welding speed can be 500~1500mm / min, specifically 1000mm / min; the scanning frequency can be 100~300Hz, specifically 200Hz; the amplitude can be 20~50mm, specifically 30mm or 40mm; and the vacuum degree can be no less than 5×10⁻⁶. -2 Pa, specifically 1×10 -2 Pa or 3×10 -2 Pa. In a vacuum environment, the preform is sealed by using the dimensional allowance of titanium-based foil at both ends to prevent titanium-based powder from overflowing during subsequent ultrasonic vibration. Three sides are sealed, leaving one side open for subsequent vacuuming.

[0045] In this invention, the process may include cleaning the preform before solder resist application; the cleaning method may be wiping, and the reagent used may be ethanol.

[0046] In this invention, the solder resist process may include the following steps: coating the surface of the preform with a solder resist agent and then drying it; the coating method may be spraying; the coating amount may be 40~120g / m². 2 The solder resist can be a boron nitride suspension or a yttrium oxide sol; when the solder resist is a boron nitride suspension, the coating amount can be 40~100 g / m². 2 When the solder resist is yttrium oxide sol, the coating amount can be 50~120g / m. 2 Air drying can be done naturally at room temperature for at least 20 minutes.

[0047] In this invention, the ultrasonic vibration-assisted hot pressing device can be a vacuum hot pressing device with ultrasonic vibration function.

[0048] In this invention, ultrasonic vibration-assisted hot pressing may include the following steps: sequentially subjecting the preform after resist welding to ultrasonic vibration powder filling, pre-pressing, vacuuming, powder degassing, fiber degumming, and hot pressing.

[0049] In this invention, the direction of ultrasonic vibration for powder filling can be unidirectional and horizontal, the vibration frequency can be 20-30 kHz (specifically 25 kHz), and the vibration amplitude can be 20-50 micrometers (specifically 30 or 40 micrometers). The duration of ultrasonic vibration for powder filling can be 30-60 seconds (specifically 40 or 50 seconds). This invention, through ultrasonic vibration for powder filling, reduces the frictional resistance between titanium-based powder particles, accelerates the particle rearrangement process, promotes the flow of titanium-based powder, and allows the titanium-based powder to better enter the internal gaps of the silicon carbide fiber bundles.

[0050] In this invention, the pre-compression pressure of the pressure head can be 5~20t, specifically 10t or 15t; the pre-compression pressure can be maintained throughout the vacuuming, powder degassing, and fiber degumming stages. This invention, through pre-compression, prevents the titanium-based powder from being extracted during the vacuuming process.

[0051] In this invention, the vacuuming time can be 1 to 3 hours, specifically 2 hours, and the vacuum level can be no less than 6 × 10⁻⁶. -3 Pa, specifically 5 × 10 -3 Pa or 3×10 -3 Pa.

[0052] In this invention, powder degassing may include sequentially performing heating degassing and heat preservation degassing; the heating rate for heating degassing can be 5~20℃ / min, specifically 10℃ / min or 15℃ / min; the heat preservation degassing temperature can be 300~600 degrees Celsius, specifically 400 degrees Celsius or 500 degrees Celsius, and the heat preservation time can be 1~5 hours, specifically 2 hours, 3 hours or 4 hours. This invention degasses titanium-based powder through powder degassing.

[0053] In this invention, fiber degumming may include sequentially performing heating degumming and heat preservation degumming; the heating rate for heating degumming can be 5~20℃ / min, specifically 10℃ / min or 15℃ / min; the heat preservation temperature for heat preservation degumming can be 500~700 degrees Celsius, specifically 550 degrees Celsius, 600 degrees Celsius or 650 degrees Celsius, and the heat preservation time can be 1~5 hours, specifically 2 hours or 4 hours. This invention removes adhesive from silicon carbide fibers through fiber degumming.

[0054] In this invention, hot pressing may include a sequential heating and pressurization stage and a heat preservation and pressure holding stage. The heating rate during the heating and pressurization stage can be 5~20℃ / min, specifically 10℃ / min or 15℃ / min. The temperature during the heat preservation and pressure holding stage can be 800~1000 degrees Celsius, specifically 850 degrees Celsius, 900 degrees Celsius or 950 degrees Celsius; the pressure (normal pressure on the preform) can be 20~100MPa, specifically 50MPa or 80MPa; and the time can be 1~5 hours, specifically 3 hours. This invention uses hot pressing to bond titanium-based powder, titanium-based aluminum foil, and silicon carbide fibers, while simultaneously densifying the titanium-based powder.

[0055] In this invention, hot pressing can be performed under ultrasonic vibration conditions; the vibration frequency of the ultrasonic vibration can be 20~25kHz, specifically 22kHz, the vibration amplitude can be 10~30 micrometers, specifically 20 micrometers, and the vibration mode can be intermittent vibration; the intermittent vibration mode can be: vibrating for 30 seconds every 10 minutes. In this invention, ultrasonic vibration is applied again during the hot pressing stage (composite material bonding stage) to improve the densification, interfacial bonding, and forming properties of the titanium-based powder: promoting creep and superplastic flow of the titanium-based powder at high temperatures, improving the metallurgical densification of the titanium-based powder; inhibiting the formation and propagation of fiber / matrix interface cracks and defects, promoting the breakage of the surface oxide layer, improving interfacial toughness, and improving the interfacial bonding of the composite material; reducing the brittleness of the composite material, improving its plastic deformation capacity, refining the material grains, inhibiting the generation of internal defects, and significantly improving the forming performance of the composite material.

[0056] In this invention, the vibration frequency of ultrasonic vibration during the hot-pressing stage is lower than that of ultrasonic vibration filling powder. This is because the increased temperature leads to changes in acoustic impedance, and the increased pressure leads to a sharp increase in contact stiffness. Lower frequencies are more likely to maintain the stable operation of the transducer under high temperature and high pressure conditions. Furthermore, lower frequencies have a larger wavelength and penetration depth, which is more conducive to the uniform transmission of ultrasonic energy in the thickness direction, promoting overall densification rather than just surface effects.

[0057] In this invention, the vibration amplitude of ultrasonic vibration during the hot pressing stage is lower than that of ultrasonic vibration for powder filling. This is because the pressure head is in close contact with the preform at this stage, and excessive amplitude may lead to accelerated wear of the pressure head or excessive frictional heat generation at the interface, resulting in localized overheating. A moderate amplitude combined with high static pressure can achieve the best densification effect and protect the silicon carbide fibers from breakage due to high-frequency, high-strain vibration.

[0058] In this invention, the total vibration time of ultrasonic vibration during the hot pressing stage is longer than that of ultrasonic vibration for powder filling. This is because the densification of titanium-based powder and the bonding at the composite material interface are thermally activated processes that require time coupling. Intermittent application of ultrasound during the heat preservation and pressure holding stages can continuously suppress the surface tension resistance in the later stages of pore closure, significantly improving density and forming performance.

[0059] In this invention, furnace cooling can include sequentially performing a pressure-holding cooling stage (referred to as the first pressure-holding cooling stage), a pressure-reducing cooling stage, and a pressure-holding cooling stage (referred to as the second pressure-holding cooling stage). The pressure of the first pressure-holding cooling stage can be 20~100MPa; the final temperature of the cooling and pressure-reducing stage can be 300~500 degrees Celsius, and the pressure reduction rate can be 1~10t / s, specifically 2t / s or 5t / s; the pressure of the second pressure-holding cooling stage can be 5~20t. Maintaining a constant pressure at the beginning of cooling aims to prevent uneven stress from causing deformation or cracking of the preform; when the temperature drops to 300~500 degrees Celsius, the pressure head is reduced, and this pressure is maintained until the preform is removed from the furnace, ensuring that the shape of the preform remains unchanged.

[0060] To further illustrate the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings and embodiments.

[0061] Example 1: This embodiment prepares a plain-weave silicon carbide fiber reinforced titanium matrix composite material (area 200×100 mm, containing 2 layers of silicon carbide fibers), the specific steps are as follows: (1) Foil polishing: Cut the titanium-based foil (TC4, thickness of 0.05 mm) to the target size, and then use low-mesh and high-mesh (500 mesh, 1000 mesh, 1500 mesh and 2000 mesh) silicon carbide sandpaper to polish away the oxide film and impurities on each surface of the titanium-based foil.

[0062] The size of the titanium-based foil does not exceed the size of the press head of the hot pressing equipment, and the foil area satisfies Equation 1 above.

[0063] The size of the middle titanium-based foil is 200×100 mm, which meets the above size requirements. In addition, two titanium-based foils are used at the top and bottom ends. Their size is 5 mm larger on each side than the size of the middle foil, that is, 210×110 mm, which is used for subsequent sealing and soldering allowance.

[0064] (2) Foil cleaning: The polished titanium-based foil is immersed in deionized water in the chamber of an ultrasonic cleaner and cleaned at room temperature for 10 minutes. The ultrasonic cleaning frequency is 35kHz and the power density is 0.65W / cm². 2 After cleaning, remove the titanium foil and place it in a dust-free environment to air dry at room temperature for 20 minutes.

[0065] (3) Powder spreading: Silicon carbide fibers (prepared by precursor conversion method, plain weave, 0.35 mm thick, 40% porosity) are cut to the same size as the intermediate titanium-based foil, i.e., 200 × 100 mm. Titanium-based powder (TC4, particle size range 0~15 μm) is evenly spread on the surface of the silicon carbide fibers. Vibration is performed using a vibration table to allow the titanium-based powder to penetrate the silicon carbide fibers and achieve initial weight gain. The vibration direction of the vibration table is horizontal unidirectional, the vibration frequency is 40 Hz, the vibration amplitude is 0.5 mm, and the vibration time is 40 seconds.

[0066] The mass of titanium-based powder incorporated into silicon carbide fibers satisfies Equation 2 above, where the density of the titanium-based powder is 4.5 g / cm³. 3 The area of ​​silicon carbide fiber is 200 cm². 2 The thickness of the silicon carbide fiber is 0.035 cm, the porosity of the silicon carbide fiber is 40%, and the powder packing density is 0.6. Calculations using Equation 2 show that the mass of titanium-based powder incorporated into the silicon carbide fiber is 7.56 g.

[0067] (4) Stacking: From bottom to top, titanium-based foil, titanium-based powder, titanium-based powder-silicon carbide fiber mixture, titanium-based powder and titanium-based foil are stacked in a cyclical manner to obtain a preform, wherein the size of the titanium-based foil at the top and bottom ends is 5 mm larger on each side than the size of the middle titanium-based foil.

[0068] The single-layer thickness of the titanium-based powder satisfies Equation 3 above, wherein the single-layer thickness of the silicon carbide fiber is 0.35 mm, the required fiber volume fraction is 50%, the single-layer thickness of the titanium-based foil is 0.05 mm, the number of silicon carbide fiber layers is 2, and the number of titanium-based foil layers, according to the stacking relationship, is... M = L +1=3; N The number of layers in the titanium-based powder is determined by the stacking relationship. N =2 L=4. The required fiber volume fraction satisfies Equation 4 above. The interface bonding correction coefficient is taken as 0.8. The calculated required fiber volume fraction is 50%. According to Equations 3 and 4, the single layer thickness of the titanium-based powder is 0.05 mm.

[0069] The thickness of a single layer of titanium-based powder is controlled by weighing, meaning the mass of each layer of titanium-based powder satisfies Equation 5, where the density of the titanium-based powder is 4.5 g / cm³. 3 The area of ​​silicon carbide fiber is 200 cm². 2 The thickness of a single layer of titanium-based powder is 0.005 cm. Calculated using Equation 5, the weight of a single layer of titanium-based powder is 4.5 g.

[0070] When laying each layer of titanium-based powder, use a clean roller to level the powder, ensuring the thickness difference does not exceed 0.01 mm.

[0071] (5) Sealing: Sealing is performed on three sides using vacuum electron beam welding. The accelerating voltage is 100kV, the electron beam current is 40mA, the focusing current is 290mA, the welding speed is 1000mm / min, the scanning frequency is 200Hz, the amplitude is 30mm, and the vacuum degree is not less than 5×10 -2 Pa.

[0072] (6) Solder resist: Wipe the titanium-based foil at both ends of the sealed preform clean with ethanol, and spray boron nitride suspension evenly with a spraying amount of 70 g / m 2 Let it air dry at room temperature for 20 minutes, and then place the preform into the furnace cavity of a vacuum hot press with ultrasonic vibration function.

[0073] (7) Ultrasonic vibration-assisted vacuum hot pressing is divided into multiple steps to achieve different effects, as follows: 1) Ultrasonic powder filling: Ultrasonic vibration is applied by a hot pressing device to allow titanium-based powder to be well inserted into the gaps between silicon carbide fibers. The direction of ultrasonic vibration is horizontal and unidirectional, the vibration frequency is 25kHz, the vibration amplitude is 30 micrometers, and the vibration time is 40 seconds.

[0074] 2) Vacuuming: First, use a 10t pressure head for pre-compression, maintaining the pre-compression pressure until the hot-compression stage. Then, begin vacuuming for 2 hours, ensuring the vacuum level inside the furnace is not lower than 6×10⁻⁶. -3 Pa.

[0075] 3) Powder degassing: Heat to 400 degrees Celsius at a heating rate of 10℃ / min and hold for 2 hours; then heat to 500 degrees Celsius at a heating rate of 5℃ / min and hold for 2 hours.

[0076] 4) Fiber degumming: Heat to 650 degrees Celsius at a heating rate of 5℃ / min and hold for 2 hours.

[0077] 5) Hot pressing: The temperature is increased to 920 degrees Celsius at a rate of 10℃ / min, at which point the pressure head also increases to 100t (based on area conversion, the normal pressure on the preform is approximately 50MPa). After reaching the temperature and pressure, it is maintained for 2 hours. Simultaneously, ultrasonic vibration is applied at a frequency of 22kHz, an amplitude of 10 micrometers, and an intermittent vibration time (vibrating for 30 seconds every 10 minutes during the pressure holding period).

[0078] 6) Cooling and depressurization: Cool down the furnace along with the furnace. Keep the pressure constant at the beginning of cooling. When the temperature drops to 400 degrees Celsius, the pressure head is reduced to 10t, and the depressurization rate is 5t / s. Then maintain this pressure until the furnace is discharged.

[0079] Comparative Example 1: The preparation method of this comparative example is the same as that of Example 1, except that the titanium-based powder is replaced with titanium-based foil, which is the same titanium-based foil as in Example 1.

[0080] Comparative Example 2: This comparative example is a silicon carbide fiber-reinforced titanium matrix composite material prepared by the conventional foil-fiber-foil method. The preparation method is the same as that in Example 1, except that titanium-based powder and ultrasonic vibration are not used.

[0081] Comparative Example 3: This comparative example is a silicon carbide fiber-reinforced titanium matrix composite material prepared by a conventional high-temperature and high-pressure powder-solid coupling method. The preparation method is the same as that in Example 1, except that ultrasonic vibration is not used.

[0082] Test Example 1: The performance of the silicon carbide fiber-reinforced titanium matrix composites prepared in Example 1 and Comparative Examples 1-3 was tested, and the test results are shown in Table 1.

[0083] Table 1. Performance comparison between Example 1 and Comparative Examples 1-3:

[0084] As shown in Table 1, the silicon carbide fiber-reinforced titanium matrix composite material prepared by the conventional foil-fiber-foil method in Comparative Example 2 has a higher porosity. Although its performance is improved compared to Comparative Example 1, the improvement is not significant. The silicon carbide fiber-reinforced titanium matrix composite material prepared by the conventional high-temperature and high-pressure powder-solid coupling method in Comparative Example 3 has a lower porosity and further improved performance, but the porosity is still close to 5%. In Example 1, ultrasonic vibration was applied, and the porosity of the prepared silicon carbide fiber-reinforced titanium matrix composite material was less than 2%, which significantly improved its performance compared to Comparative Example 1 and can meet the service requirements of high-performance components.

[0085] Test Example 2: The microstructure of the silicon carbide fiber-reinforced titanium matrix composite material prepared in Example 1 was observed, and the results are as follows: Figures 3-5 As shown, where, Figure 3 The microstructure of titanium-based powder in silicon carbide fiber-reinforced titanium matrix composites. Figure 4 The microstructure of radial interfacial bonding in silicon carbide fiber-reinforced titanium matrix composites. Figure 5 The microstructure of the axial interfacial bonding of silicon carbide fiber reinforced titanium matrix composites.

[0086] from Figure 3 It can be seen that in the silicon carbide fiber-reinforced titanium matrix composite material prepared in Example 1, the titanium matrix powder achieved a very good densification effect, with no defects such as pores or porosity observed, and it consisted of equiaxed and lath structures. Figure 4 and Figure 5 It can be seen that the silicon carbide fibers and titanium matrix are tightly bonded in both the radial and axial directions, with no obvious defects observed. These results demonstrate that the ultrasonic-assisted powder-solid coupling molding method provided by this invention can simultaneously and effectively achieve both titanium matrix powder densification and the bonding between silicon carbide fibers and the titanium matrix.

[0087] As can be seen from the above embodiments and comparative examples, the ultrasonic-assisted powder-solid coupling molding method of the present invention can overcome the limitations of conventional technology in filling the gaps between bundled fibers, reduce the internal porosity in silicon carbide fiber-reinforced titanium matrix composites, and ultimately obtain high-performance composite material components with fewer defects.

[0088] The embodiments of the present invention have been described above; however, these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. All other embodiments obtained by those skilled in the art based on the above embodiments of the present invention without inventive effort are within the protection scope of the present invention.

Claims

1. An ultrasonic-assisted powder-solid coupling molding method for silicon carbide fiber-reinforced titanium matrix composites, characterized in that, Includes the following steps: (1) Cut silicon carbide fibers to the same length as titanium-based foil, then spread titanium-based powder on the surface of silicon carbide fibers and vibrate to obtain a mixture of titanium-based powder and silicon carbide fibers; (2) The titanium-based foil, titanium-based powder, titanium-based powder-silicon carbide fiber mixture, titanium-based powder and titanium-based foil are stacked in the order of titanium-based foil to obtain the preform; (3) The preform is sequentially sealed, resisted, ultrasonically vibrated hot pressing and furnace cooling to obtain silicon carbide fiber reinforced titanium matrix composite material.

2. The ultrasonic-assisted powder-solid coupling forming method according to claim 1, characterized in that, The silicon carbide fiber is prepared by the precursor conversion method; the silicon carbide fiber is in the form of bundled filaments or braided filaments; the thickness of the silicon carbide fiber is 0.01~1 mm.

3. The ultrasonic-assisted powder-solid coupling forming method according to claim 1, characterized in that, The particle size of the titanium-based powder is no greater than 53 micrometers.

4. The ultrasonic-assisted powder-solid coupling forming method according to claim 1, characterized in that, The vibrating device is a vibration table; the vibration direction is horizontal and unidirectional, the vibration frequency is 30~50Hz, the vibration amplitude is 0.4~0.7 mm, and the vibration time is 30~60 seconds.

5. The ultrasonic-assisted powder-solid coupling forming method according to claim 1, characterized in that, The stacking cycle is more than 1 time; when the stacking cycle is more than 2 times, the same layers are not adjacent.

6. The ultrasonic-assisted powder-solid coupling forming method according to claim 1, characterized in that, The sealing process is vacuum electron beam sealing; the accelerating voltage is 50~150kV, the electron beam current is 10~50mA, the focusing current is 200~500mA, the welding speed is 500~1500mm / min, the scanning frequency is 100~300Hz, the amplitude is 20~50mm, and the vacuum level is not less than 5×10⁻⁶. -2 Pa.

7. The ultrasonic-assisted powder-solid coupling forming method according to claim 1, characterized in that, Ultrasonic vibration-assisted hot pressing includes the following steps: ultrasonic vibration filling of the preform after resist welding, pre-compression, vacuuming, powder degassing, fiber degumming and hot pressing.

8. The ultrasonic-assisted powder-solid coupling forming method according to claim 7, characterized in that, The ultrasonic vibration powder filling direction is horizontal and unidirectional, the vibration frequency is 20~30kHz, the vibration amplitude is 20~50 micrometers, and the ultrasonic vibration powder filling time is 30~60 seconds.

9. The ultrasonic-assisted powder-solid coupling forming method according to claim 7, characterized in that, Hot pressing includes a heating and pressurization stage followed by a heat preservation and pressure holding stage. The heating rate during the heating and pressurization stage is 5~20℃ / min. The temperature during the heat preservation and pressure holding stage is 800~1000℃, the pressure is 20~100MPa, and the time is 1~5 hours. Hot pressing is performed under ultrasonic vibration conditions. The ultrasonic vibration frequency is 20~25kHz, the vibration amplitude is 10~30 micrometers, and the vibration mode is intermittent vibration. The intermittent vibration mode is: vibrating for 30 seconds every 10 minutes.

10. The ultrasonic-assisted powder-solid coupling forming method according to claim 1, characterized in that, The furnace cooling process includes a first pressure holding and cooling stage, a pressure reduction and cooling stage, and a second pressure holding and cooling stage. The pressure in the first pressure holding and cooling stage is 20~100MPa. The final temperature of the cooling and pressure reduction stage is 300~500 degrees Celsius. The pressure in the second pressure holding and cooling stage is 5~20t.

Citation Information

Patent Citations

  • Preparation method of SiC woven fiber reinforced titanium-based composite material plate

    CN116329555A

  • Preparation method of SiC fiber reinforced Ti-based composite ultrathin laminated plate

    CN120756182A

  • Preparation method of continuous SiC fiber reinforced titanium-based composite material plate

    CN122327107A